2016
DOI: 10.1097/sih.0000000000000173
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Disaster Day

Abstract: Summary Statement Disaster Day is a simulation event that began in the College of Nursing and has increased exponentially in size and popularity over the last eight years. The evolution has been the direct result of reflective practice and dedicated leadership in the form of students, faculty, and administration. Its development and expansion into a robust interprofessional education activity is noteworthy as it gives healthcare professions students an opportunity to work in teams to provide care in a disaster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…With the occurrence of a number of major disasters around the world over the past 40 years, including the COVID-19 pandemic, there is a growing need for disaster training [1][2][3][4][5][6][7][8][9][10][11][12]. Accordingly, various disaster medicine educational programs have been developed and their effectiveness has been tested [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the occurrence of a number of major disasters around the world over the past 40 years, including the COVID-19 pandemic, there is a growing need for disaster training [1][2][3][4][5][6][7][8][9][10][11][12]. Accordingly, various disaster medicine educational programs have been developed and their effectiveness has been tested [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…With the occurrence of a number of major disasters around the world over the past 40 years, including the COVID-19 pandemic, there is a growing need for disaster training [1][2][3][4][5][6][7][8][9][10][11][12]. Accordingly, various disaster medicine educational programs have been developed and their effectiveness has been tested [1][2][3][4][5][6][7][8][9][10][11][12]. In particular, chemical disasters, such as the Seveso dioxin leakage disaster in Italy, the methyl isocyanate leakage disaster in Bhopal, India, and the Gumi fluoric acid gas leakage disaster in Korea in 2012, have attracted a great deal of attention worldwide [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In 34 Interprofessional "Disaster Day" simulations, developed at Texas A&M Health Sciences Center, 35 are examples of innovative methods for incorporating this content into existing curricula.…”
Section: Discussionmentioning
confidence: 99%
“…Educational training in disaster preparedness has typically engaged healthcare students in medicine, nursing, and pharmacy (8,9). Multiple studies have shown that interprofessional disaster simulation scenarios can be effective tools to build confidence and readiness in disaster response (10)(11)(12)(13). Healthcare education has embraced the need for interprofessional education (IPE) and Interprofessional Education Collaborative (IPEC) core competencies are now found in many healthcare disciplines (14).…”
Section: Introductionmentioning
confidence: 99%